The use of social media and its relationship to the phenomenon of violence in the school environment (a field study on a sample of secondary schools in Tebessa Province) - mebarkia, ossama (Journal of Social Sciences and Humanities, 2025)
This study aimed to shed light on social networking sites and their relationship to the phenomenon of violence in the school environment. The study followed the descriptive approach appropriate to the nature of the subject, and was applied to a sample of 90 individuals of both sexes, and was treated statistically using the (SPSS) program, version No. (28). The results of the study revealed that there is a close relationship between social networking sites and the phenomenon of violence in the school environment.